2019
DOI: 10.1177/1934578x19848168
|View full text |Cite
|
Sign up to set email alerts
|

Jatrophane Diterpenoids With Protective Effect on Human Lymphocytes DNA

Abstract: Two sets of structurally different jatrophanes (1-11 and 13-16), jatrophane 12, and latex extract of 2 Euphorbia species (17 and 18) were tested for in vitro protective effect against chromosome aberrations in peripheral human lymphocytes using the cytokinesis-block micronucleus (CBMN) assay. Jatrophanes 1-6 in minimal doses of 1 µg/mL prominently decreased micronuclei (MN) frequency in the range 44.86% to 34.29% and manifested considerable protective effect. From the other set of jatrophanes, 13 in the same m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…slightly decreases, which was not the case with the previously studied jatrophanes and sesquiterpene lactones (Krstić et al 17 and Cvetković et al 18 , respectively). Typical DNA protective activity of natural products is mostly attributed to their antioxidative potential.…”
Section: O N L I N E F I R S Tmentioning
confidence: 56%
See 2 more Smart Citations
“…slightly decreases, which was not the case with the previously studied jatrophanes and sesquiterpene lactones (Krstić et al 17 and Cvetković et al 18 , respectively). Typical DNA protective activity of natural products is mostly attributed to their antioxidative potential.…”
Section: O N L I N E F I R S Tmentioning
confidence: 56%
“…Typical DNA protective activity of natural products is mostly attributed to their antioxidative potential. [15][16][17][18] The cytotoxic and antioxidant activity of nine lanostane-type triterpenes, isolated from P. cocos, were examined previously by Zhou et al 20 They tested the ability of scavenging free oxygen radicals and inhibition of oxidation using DPPH (2,2-diphenyl-1-picrylhydrazyl) radical test. In comparison to the vitamin E used as a positive control, the compounds tested did not show antioxidant activity with p<0.05 that may be considered statistically significant.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…135,341 Among them, euphodendrophanes A ( K57 ), B ( K58 ), H ( 414 ), I ( 415 ), K ( 418 ), and O ( 422 ), prominently decreased micronuclei frequency and manifested considerable protective effect. 342 Euphorbesulin G ( 465 ) displayed potent antimalarial effect against chloroquine-resistant Plasmodium falciparum strain with an IC 50 value of 0.12 μM. 111…”
Section: Biological Activitiesmentioning
confidence: 99%
“…These observations agreed with Kulig et al’s [ 111 ] assertion that vicinal diol groups contribute significantly to the bioactivities of naturally occurring compounds possessing them. Other studies on the structure–activity relationship of jatrophane diterpenoids showed that substitution of a benzoate at C-8 and C-9 are favorable, while isobutanoyloxy group substitution at C-3 increased the observable effects on human lymphocytes deoxyribonucleic acid (DNA) [ 112 ].…”
Section: Pharmacological Activities and Structure–activity Relationship (Sar)mentioning
confidence: 99%